COGNITIVE FEATURES OF ETHNONYMS - Nurtayeva Zebuniso (PEDAGOGS, 2024)
Abstract. Ethnonyms, the names used to identify and refer to ethnic groups, carry profound cognitive implications that extend far beyond mere labels. Embedded within these seemingly simple terms are complex webs of identity, perception, and cultural constructs, shaping how individuals and societies perceive themselves and others. Exploring the cognitive features of ethnonyms unveils the intricate interplay between language, culture, and cognition, offering insights into the multifaceted nature of human categorization and social dynamics.